PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PADA KLINIK HOUSE OF PHYTO SEMARANG - Eko Budi Setiawan, 09.05.51.0005 (Students Journal of Economic and Management, 2014)
The purpose of the study titled "The Effect of Service Quality and Corporate Image on Customer Satisfaction ( Study At House Of Phyto Clinic in Semarang ) " is to examine and analyze the effect on the image quality of service and customer satisfaction .Data used in this study is primary data obtained directly from the original source . While the techniques used to collect data using a questionnaire by asking a number of written questions used to obtain information of the respondents. The sample used in this study were 100 respondents with sempel retrieval technique was purposive sampling , the criteria respondents who become customers clinic House of phyto ( already doing more treatments of1 times ) dijalain Brotojoyo 4D/15 cottage Indraprasta Semarang . The collected data were analyzed by using AnalisisFaktor to test the validity of the question items , Cronbach s Alpha formula for reliability testing instruments and multiple linear regression analysis .The results of the hypothesis : ( 1 ) Quality of service and no significant positive effect on the customer satisfaction ( 2 ) Corporate Image and significant positive effect on customer satisfaction . Keywords : Quality of Service , Image , and Customer Satisfaction